2020
DOI: 10.1016/j.patter.2020.100139
|View full text |Cite
|
Sign up to set email alerts
|

scTenifoldNet: A Machine Learning Workflow for Constructing and Comparing Transcriptome-wide Gene Regulatory Networks from Single-Cell Data

Abstract: Highlights d scTenifoldNet is a machine learning tool for comparative single-cell network analysis d It is built upon PC regression, tensor decomposition, and manifold alignment d It constructs and compares gene regulatory networks from scRNA-seq data d It accurately identifies differentially regulated genes between single-cell samples

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 89 publications
(161 reference statements)
0
35
0
Order By: Relevance
“…Step 1: Constructing scGRN with scRNAseq data from WT samples With the scRNAseq data from a WT sample, scTenifoldKnk first constructs an scGRN using a pipeline we proposed previously, namely, scTenifoldNet. 9 This network construction step contains three sub-steps (Figure 1A):…”
Section: Results 1: the Sctenifoldknk Workflowmentioning
confidence: 99%
See 2 more Smart Citations
“…Step 1: Constructing scGRN with scRNAseq data from WT samples With the scRNAseq data from a WT sample, scTenifoldKnk first constructs an scGRN using a pipeline we proposed previously, namely, scTenifoldNet. 9 This network construction step contains three sub-steps (Figure 1A):…”
Section: Results 1: the Sctenifoldknk Workflowmentioning
confidence: 99%
“…We have previously shown that scRNAseq information can be leveraged to fuel the machine learning algorithms for reliable scGRN construction. 9 In a GRN, the regulatory effect manifests as observable synchronized patterns of expression between genes. These genes are associated with the same biological process, pathway, or under the control of the same set of TFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To systematically compare macrophage transcriptomes between M and S patient groups, we employed a machine learning workflow-named scTenifoldNet (Fig. 1d), which we developed to construct and compare single-cell gene regulatory networks (scGRNs) [14]. The most important advantage of this network-based comparative analytical framework is its sensitivity.…”
Section: Main Textmentioning
confidence: 99%
“…The most important advantage of this network-based comparative analytical framework is its sensitivity. We have shown that scTenifoldNet can detect differential regulatory patterns between highly similar scRNA-seq samples to reveal gene regulatory changes, which are undetectable otherwise [14]. scTenifoldNet is built upon several machine learning methods including principal component regression, low-rank tensor approximation, and manifold alignment (Fig.…”
Section: Main Textmentioning
confidence: 99%